2016
DOI: 10.1128/jb.00193-16
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Residues Contribute to Motility Repression and Autoregulation in the Proteus mirabilis Fimbria-Associated Transcriptional Regulator AtfJ

Abstract: Proteus mirabilis contributes to a significant number of catheter-associated urinary tract infections, where coordinated regulation of adherence and motility is critical for ascending disease progression. Previously, the mannose-resistant Proteus-like (MR/P) fimbria-associated transcriptional regulator MrpJ has been shown to both repress motility and directly induce the transcription of its own operon; in addition, it affects the expression of a wide range of cellular processes. Interestingly, 14 additional mr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…Notably, MrpJ paralogs are not restricted to P. mirabilis as they have been detected in fimbrial operons from related genera (264266). Because fimbriae allow bacteria to adhere or form biofilms in specific environments, and thus respond to niche-specific signals, MrpJ paralogs have been proposed to orchestrate genetic programs that are beneficial to those environments (132, 267). …”
Section: Virulence Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Notably, MrpJ paralogs are not restricted to P. mirabilis as they have been detected in fimbrial operons from related genera (264266). Because fimbriae allow bacteria to adhere or form biofilms in specific environments, and thus respond to niche-specific signals, MrpJ paralogs have been proposed to orchestrate genetic programs that are beneficial to those environments (132, 267). …”
Section: Virulence Factorsmentioning
confidence: 99%
“…Like MrpJ itself, the MrpJ paralogs regulate other fimbrial operons in addition to repressing motility (267). Screening of MrpJ, UcaJ, AtfJ, and Fim8J showed that some paralogs positively auto-regulate their operons.…”
Section: Virulence Factorsmentioning
confidence: 99%
See 3 more Smart Citations